Counselling intervention to address school bullying: a systematic review of literature - Lai, Wei Foon; Hassan, Siti Aishah; Mohamed Nordin, Mohd Hamdan (Human Resource Management Academic Research Society, 2020)
Bullying is a significant concern to the society and in schools these days. Both bullies and victims are at risk for negative developmental outcomes. School counsellors are facing many challenges to identify the warning signs and subsequently to address them efficiently. There are empirical studies on school-based bullying prevention programs and specific counselling approach to attend to this phenomenon. However, mixed findings were found on the effectiveness of both approaches to address school bullying issues. Ten articles were selected to identify 1) The role of school bullying prevention program to counselling services, 2) the role of school counsellors and their challenges in addressing bullying and 3) students’ response to the role of counsellor on bullying. Based on this review, the implications to multicultural counselling were also being discussed.